Narrativas de professoras que ensinam matemática na região de Blumenau (SC): sobre as feiras catarinenses de matemática e as práticas e e concepções sobre ensino e aprendizagem de matemática - Silva, Viviane Clotilde da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research aims to present and analyze narratives that, as a whole, allowed assigning meaning to conceptions and practices related to the teaching and learning of mathematics in the elementary schooling system in the State of Santa Catarina. In this scenario, the Mathematics Fairs of Santa Catarina are noteworthy. Drawing on the methodology known as Oral History, were collected, edited and studied depositions of (a) fifteen active teachers at the beginning of formal schooling, all of them involved with mathematics fairs and (b) one of the creators and current coordinator of the fairs. It was also used as sources to our study specific documents (reports, minutes, proceedings and books) about the fairs. With this approach, we can understand - even if only partially, as necessarily occurs in studies that have conceptions as their central theme - aspects of conceptions of mathematics and how teaching and learning of Mathematics is effectively occurring in schools, how these conceptions materialize in practices and how practice works to create conceptions. We also draw a Historiography of Mathematics Fairs of Santa Catarina, talking such historiography as a narrative. Extending the notion of historiography, this narrative not only lists and reissue information available in written sources, but incorporates the experiences reported by our respondents, important not only to understand the event, but as a possible contribution to its review.

Esta pesquisa tem por objetivo apresentar e analisar narrativas que, em seu conjunto, permitiram atribuir significado a concepções e práticas atualmente vigentes relacionadas ao ensino e à aprendizagem de matemática nos anos iniciais, em escolas do estado de Santa Catarina. Valendo-se da metodologia conhecida como História oral, foram coletados, editados e estudados depoimentos de quinze professoras atuantes no início da escolarização formal que têm ou tiveram envolvimento com as Feiras de Matemática ao longo dos vintes e cinco anos de desenvolvimento desse evento e (b) de um dos criadores e atual coordenador das Feiras, além de documentos (relatórios, atas, anais e livros) específicos sobre elas. Com esse enfoque, pudemos compreender - ainda que parcialmente, como ocorre necessariamente nos estudos que têm concepções como tema central - aspectos das concepções sobre a Matemática e como se desenvolve seu ensino e aprendizagem nas escolas e, ao mesmo tempo, traçar uma Historiografia das Feiras Catarinenses de Matemática. Ampliando a noção de Historiografia, essa narrativa sobre as Feiras não apenas enumera e reedita informações disponíveis em fontes escritas, mas incorpora as experiências relatadas pelas depoentes, fundamentais não apenas para compreender o evento, mas como possívl contribuição para sua avaliação.
Keywords: Educação; Matemática; Professores - Formação; Historia oral; Education